Spatial and temporal variabilities of spring Asian dust events and their impacts on chlorophyll‐a concentrations in the western North Pacific Ocean. Issue 3 (15th February 2017) - Yoon, Joo‐Eun; Kim, Kitae; Macdonald, Alison M.; Park, Ki‐Tae; Kim, Hyun‐Cheol; Yoo, Kyu‐Cheul; Yoon, Ho‐Il; Yang, Eun Jin; Jung, Jinyoung; Lim, Jae‐Hyun; Kim, Ju‐Hyoung; Lee, Jiyoung; et al.
Abstract: As the western North Pacific Ocean is located downwind of the source regions for spring Asian dust, it is an ideal location for determining the response of open waters to these events. Spatial analysis of spring Asian dust events from source regions to the western North Pacific, using long‐term daily aerosol index data, revealed three different transport pathways supported by the westerly wind system: one passing across the northern East/Japan Sea (40°N–50°N), a second moving over the entire East/Japan Sea (35°N–55°N), and a third flowing predominantly over the Siberian continent (>50°N). Our results indicate that strong spring Asian dust events can increase ocean primary productivity by more than 70% (>2‐fold increase in chlorophyll‐ a concentrations) compared to weak/nondust conditions. Therefore, attention should be paid to the recent downturn in the number of spring Asian dust events and to the response of primary production in the western North Pacific to this change. Key Points: There were three different transport pathways for spring Asian dust events in the study area Ocean primary productivity was significantly increased by the spring Asian dust events There has been a recent decrease in spring Asian dust events in the western North Pacific Ocean